First clinical experiences with a novel endoscopic over-the-scope clip system - Dinelli, Marco; Omazzi, Barbara; Andreozzi, Paolo; Zucchini, Nicola; Redaelli, Alessandro; Manes, Gianpiero (Endoscopy International Open, 2017)
We describe our experience with a new over-the-scope clip (OTSC) system (Padlock Clip™) in the treatment of 14 patients. Eight of the 14 patients were treated for closure of gastrointestinal fistulas (n = 4), iatrogenic gastrointestinal perforations (n = 2), or hemostasis of post-polypectomy bleeding (n = 2). The site of clipping was the lower gastrointestinal tract in five patients and the upper gastrointestinal tract in three patients. The clip was successfully delivered in seven out of the eight patients and clinical success was achieved in all patients. Endoscopic full thickness resection (EFTR) was performed to treat six patients: four with recurrent adenoma (n = 4), one with ulcerated nodules at ileorectal anastomosis, and one with a neuro-endocrine tumor of the rectum. A complete intestinal wall resection was achieved in three of the six patients (50 %) and an R0 resection in five of the six patients (83.3 %). No complications related to the procedure and no recurrence at endoscopic follow-up were observed in any patient. The novel Padlock Clip seems to be an effective and safe tool to treat gastrointestinal fistulas, perforations or post-polypectomy bleeding, and to perform EFTR.